Menjaga Wajah Islam Asia Tenggara: Peran MABIMS dalam Harmonisasi Hilal, Halal, dan Ideologi Wasathiyah - Akbar, Reza; Nurhafiza, Nurhafiza; Katsirin, Khairul (Jurnal Global Futuristik, 2026)
The discourse on religious diplomacy and the governance of Islamic law in the Southeast Asian region cannot be separated from the institutional role played by the forum of Religious Ministers of Brunei Darussalam, Indonesia, Malaysia, and Singapore (MABIMS). Since its establishment in 1989, MABIMS has evolved from a mere informal consultative forum into a strategic platform facilitating the harmonization of regional Islamic policies amidst the dynamics of globalization and geopolitical challenges. This research report aims to comprehensively identify, analyze, and evaluate the strategic role of MABIMS in responding to the contemporary problems of Muslims in Southeast Asia. This research is structured adhering to strict academic guidelines, focusing the analysis on three main pillars: the unification of the Hijri calendar, the standardization of the halal industry ecosystem, and the mainstreaming of religious moderation (Islam Wasathiyah). This study uses a qualitative literature-based research method (library research) with a normative-juridical and historical approach. Data were collected through critical reading of official MABIMS resolution documents, Islamic journals, and public policy literature from member countries. The identification results indicate that MABIMS plays a central role in: (a) ratifying the New Criteria for hilal visibility (minimum altitude of 3 and elongation of 6.4) to reduce disparities in Islamic holiday celebrations and unify the regional Islamic astronomy (Ilmu Falak) paradigm; (b) harmonizing cross-border halal certification standards to strengthen the ASEAN region's position as the epicenter of the global sharia economy; and (c) strengthening soft power diplomacy through integrated Hajj management and the promotion of Islam Wasathiyah as an antithesis to transnational extremism and puritanism. The main conclusion of this study emphasizes that although MABIMS resolutions are conceptually and normatively very ideal, their implementation at the grassroots level still collides with sociological obstacles, methodological pluralism, local traditional heritage, and the political sovereignty of each country. Therefore, social engineering strategies and the transformation of resolutions into more binding legal instruments are needed to ensure a real and measurable impact on the unity and welfare of Muslims in the Nusantara region.